2003
DOI: 10.1002/micr.10126
|View full text |Cite
|
Sign up to set email alerts
|

Loupes‐only microsurgery

Abstract: Standard magnification in microsurgery is accomplished with the operating microscope. Loupes are perceived by the microsurgical community as technically less safe. However, after several years of microscope-only microsurgery, most of our microvascular procedures are performed under loupes 3.5-4x. Considering our results using loupes-only microsurgery, which are comparable with those obtained when using the microscope, we suggest that loupe-aided microsurgery might represent a natural progression for the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 19 publications
0
25
0
2
Order By: Relevance
“…Microsurgical skills and experience outweigh the importance of the magnification factor''. 20 Not all research supports this view, however. A study quantitatively investigating precision of an orthosis task using 93.5-4.0 loupe magnification and 98-30 microscope magnification concluded that the mean accuracy was higher to a statistically significant degree in the group using the higher magnification microscopes.…”
Section: Visual Feedback and Accuracymentioning
confidence: 75%
“…Microsurgical skills and experience outweigh the importance of the magnification factor''. 20 Not all research supports this view, however. A study quantitatively investigating precision of an orthosis task using 93.5-4.0 loupe magnification and 98-30 microscope magnification concluded that the mean accuracy was higher to a statistically significant degree in the group using the higher magnification microscopes.…”
Section: Visual Feedback and Accuracymentioning
confidence: 75%
“…Pieptu and Luchian stated that microsurgical techniques should be used for the creation of AVFs, irrespective of the level of the anastomosis. 29 Margic supported the use of microsurgical techniques in the creation of AVFs because of the effects of ESRD on the vasculature. 30 Pieptu and Luchian recommended wide-field loupes as the first choice for most anatomoses, but suggested the use of a microscope for thinwalled vessels or diseased vasculature.…”
Section: Discussionmentioning
confidence: 98%
“…30 Pieptu and Luchian recommended wide-field loupes as the first choice for most anatomoses, but suggested the use of a microscope for thinwalled vessels or diseased vasculature. 29 Bourquelot et al reported that with the use of a microscope, the vascular dissection and creation of anastomoses are made easier. 6 The microscope and the use of preventative hemostasis, such as with an inflatable tourniquet, allow the creation of AVFs even in children under 5 kg in weight.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to their favorable outcomes, while using surgical loupes in "macro-microsurgery," Pieptu and Luchian acknowledged the ability to use loupes while performing replantations proximal to the palmar arch and in free flaps with vessel diameter greater than 1.5 mm. 3 In summary, while the literature lacks studies allowing strong evidence-based recommendations, several key points can be drawn: 1. Technical skill and experience developed using the surgical microscope is necessary before loupeassisted microsurgery. 2.…”
Section: Discussionmentioning
confidence: 99%